2020
DOI: 10.12691/ajmcr-8-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana-induced Coronary Vasospasm and Myocardial Infarction: A Case Report and Review of Literature

Abstract: The usage of marijuana and its legalization has been growing rapidly, being abused by a wide range of age groups. Its effects on the heart are well known, but coronary artery vasospasm causing ST elevation myocardial infarction (STEMI) from Marijuana alone is rather lesser known. Herein, we report a case of a middle aged African American man with a significant tobacco smoking history who presented with chest pain typical of myocardial infarction (MI) soon after smoking marijuana. ECG showed ST elevation in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…There was an elevation of ST-segment in electrocardiogram (EKG) leads II, III, and aVF and ST-segment depression in leads of aVL, V4, and V5. They diagnosed it as ST-segment Elevation Myocardial Infarction (STEMI)[31]. Yurtdaş et al reported a case of a 26-year-old male who came to their clinic with complaints of radiating chest pain to both his upper limbs.…”
mentioning
confidence: 99%
“…There was an elevation of ST-segment in electrocardiogram (EKG) leads II, III, and aVF and ST-segment depression in leads of aVL, V4, and V5. They diagnosed it as ST-segment Elevation Myocardial Infarction (STEMI)[31]. Yurtdaş et al reported a case of a 26-year-old male who came to their clinic with complaints of radiating chest pain to both his upper limbs.…”
mentioning
confidence: 99%